Expectations of the Transatlantic Trade and Investment Partnership macroeconomic effects: an attempt to provide constructive assessment (Economic and Political Thought, 2016)
The main purpose of the paper is to provide a critical overview and analysisof literature concerning expected and predicted macroeconomic effectsof the TTIP on the EU and the US. The paper contains information onthe main points that are being negotiated by the representatives of the EUand the US. We also try to shed some light on the social expectations of theTTIP, which we discuss with reference to Eurobarometer and BertelsmannFoundation survey results. The CGE model results together with the critiqueand macroeconomic consequences of the TTIP are captured, too. Moreover,these are compared to the experience of NAFTA – the agreement betweenthe USA, Canada and Mexico, which has been in force for 22 years now.A comparative analysis of NAFTA ex ante models and the results of empiricalresearch ex post shows that most ex ante models overestimated benefitsand underestimated losses of the Free Trade Agreement. NAFTA experienceemphasises weaknesses of ex ante models and shows that a mismatchbetween real and estimated effects of NAFTA can be an indicative answerto the question about the scale of a mismatch between the TTIP prospectiveand real influence.